Comparison of carbon sources in a partial denitrification/anammox MBBR using glycerol, acetate, and methanol. Issue 4 (3rd March 2023) - Klaus, Stephanie; Campolong, Cody; Rosenthal, Alex; Sabba, Fabrizio; Baideme, Matthew; Wells, George; De Clippeleir, Haydee; Chandran, Kartik; Bott, Charles
Abstract : Mainstream partial denitrification/anammox MBBR with nitrate-based carbon dosing control. Abstract : Partial denitrification/anammox (PdNA) is an emerging treatment process that can act as a supplement to, or in place of partial nitritation anammox for implementation in mainstream wastewater. A pilot scale PdNA moving bed biofilm reactor (MBBR) was operated at 20 °C. Glycerol, acetate, and methanol were evaluated as external carbon sources. Average PdN efficiency was 88% ± 13 with glycerol, 86% ± 10 with acetate, and 66% ± 11 with methanol. Contrary to previous reports, methanol was not inhibitory to anammox activity. The COD added per TIN removed was 2.41 ± 0.98, 2.02 ± 0.71, and 1.73 ± 0.81 g COD g N −1 for glycerol, acetate, and methanol respectively. During the methanol phase influent nitrite decreased the COD requirement, demonstrating that the polishing MBBR supports both two-stage PNA and single stage PdNA simultaneously. When only considering the PdNA route, methanol still had a comparable COD added/TIN removed ratio to the other two carbon sources (2.33 ± 0.95 g COD g N −1 ) despite having the lowest PdN efficiency. Appropriate control of influent ammonia to NO x ratio was the limiting factor to reaching low effluent TIN concentrations and maintaining a residual nitrate setpoint via automated carbon dosing control was necessary. Results demonstrate that PdNA is a promising and carbon-efficient technology for nitrogen polishing which can be implemented with a variety of carbon sources, with or without upstream nitrite accumulation.